Did Edward Said’s Orientalism inaugurate a new kind of study of colonialism? - Arthur, Leah (Kent Law Review, 2022)
Jozsef Borocz and Mahua Sarkar’s definition of colonialism acknowledges that it is simultaneously a practice and a worldview. In practice, colonialism refers to “the domination of a society by settlers from a different society” whereas as a worldview it is a “global geopolitical, economic and cultural doctrine that is rooted in the worldwide expansion of West European capitalism that survived until well after the collapse of most colonial empires”.[1] The latter definition alludes to the fact that the effects of colonialism have a long-lasting influence on the countries and people that have experienced said system. These effects are what postcolonialism encapsulates. Postcolonial theory revolves around the “political, aesthetic, economic, historical and social impact of European colonial rule”.[2] It is seen as highlighting “the colonial experience from the colonised society’s point of view.”[3] Edward Said is widely recognised to be one of the central scholars within the postcolonial field. Born in Western Jerusalem in 1935, this Palestinian American Professor of English and Comparative Literature, and Political Activist, is often recognised to be a founding figure in the development of postcolonial theory. While Said’s diverse background often left him feeling ‘out of place’, he managed to turn this alienation into a tool that benefitted his work.[4] His prestigious Western education coupled with his Middle Eastern background created a distinct point of view of the West and colonialism.[5] This unique perspective was mirrored in his ground-breaking book, Orientalism[6]. Published in 1978, Orientalism was extremely critical of our understandings of the West and its relationship with the East. Said presented three interpretations of orientalism: as a field of study; as a binary opposition between the Occident and Orient; and, as a Western tool of authority and power. These definitions have been both conformed to and heavily criticized in the years since publication. However, the impact of Orientalism is unquestionable and often credited to be the foundation upon which the study of postcolonialism developed. With this in mind, this essay will seek to answer the question of whether Said’s Orientalism inaugurated a new study of colonialism. It will consider the prominent studies of colonialism in the pre-Orientalism era, the new ideas Orientalism presented and its influence on the development of postcolonialism, the arguments against the idea of it being a new field of study, and lastly, its influence on successive postcolonial theorists. BEFORE SAID In order to appreciate the new ideas presented by Said, one must first acknowledge some of the major theories revolving around colonialism that preceded it. Discussions of colonialism generally found their roots in advancing Western superiority and saw any deviation from the associated ideals as inferior. A presiding theme that generally arose can be described as Rudyard Kipling’s “white man’s burden”, where the West believed that they had no choice but to colonise in order to ensure that Western ideals were instilled in others.[7] Evidence of this ‘saviour mentality’ is found in the 16th century Valladolid Debate.[8] Deemed the first moral debate in European history, it dealt with the Spanish rights to conquest and the treatment of the indigenous Indians. Juan Gines de Sepulveda argued that the Spanish had a “right to rule” because of the barbaric, ignorant and unreasoning nature of the Indians.[9] These views were mirrored in the work of Denis Diderot and his concept of the “noble savage”.[10] Diderot’s “noble savage” acknowledged indigenous people to operate by nature and are therefore to be inherently good despite being uncivilised. While this seemed advantageous, it actually created high expectations of what indigenous people would be like and subsequent disappointment, which fuelled an idea that this noble savage was a myth.[11] Previous theories of orientalism also aligned with these ideas. As noted by Hector Roddan “[b]efore Said, orientalism referred to the study of the history, language and culture of ancient and modern Asiatic societies”.[12] Said highlighted the work of two orientalists: Arthur James Balfour and Lord Cromer. Both theorists saw the Orient as irrational, childlike and thus in need of guidance.[13] Furthermore, they felt that these characteristics could be universally applied to any Orient, regardless of their peculiarities. Both Balfour and Cromer’s theories of orientalism revolved around knowledge and power. As highlighted by Said, Balfour believes that “England knows Egypt” and that “Egypt is what England knows”.[14] This knowledge translates into a justification for domination and authority through colonialism and occupation.[15] Cromer’s theory was based on his direct experiences with these ‘subject races’. In addition to knowledge, the colonised-coloniser relationship for Cromer was based on Western strength. He saw the Orient solely as something to govern, upon which the strength of the West could be inflicted.[16] He believed that their ideals were unnatural and to remain with such a belief system would be detrimental as they did not know what was good for themselves.[17] SAID’S ORIENTALISM The claim that Said inaugurated a new kind of study of colonialism stems from the fact that his orientalism compels us to question the accuracy of those depictions put forward in literature. From the beginning Said criticizes the existing concepts of the Orient, referring to it as a “European invention”.[18] He also acknowledges multiple understandings which overlap to bring coherency to the theory. These revolve around orientalism being an academic discipline, a relationship between the Orient and Occident, and a tool for Western domination. Within these definitions, we also see key ideas being introduced such as the distinction between latent and manifest orientalism and worldly criticisms of literature. Said relied on Foucault’s theory of discourse, which is explained as “a way of organising knowledge that structures the constitution of social relations through collective understanding of the discursive logic and acceptance of the discourse as social fact.”[19] This implies a relationship between knowledge and power through the management of what society knows and accepts. In the Order of Things Foucault questioned what it means for an idea to represent a particular thing.[20] Through the acknowledgement of such, he hoped to develop more accurate understandings of society.[21] This is also what Said seeks to achieve in Orientalism: acknowledging the ideas of orientalism as inaccurate, Western-made depictions of the East, and challenging the discourse to bring about more accurate representations of Oriental societies. Orientalism as a Discipline Said provides an extremely broad definition of orientalism as an academic discipline, arguing that “[a]nyone who teaches, writes about or researches about the Orient…either in its specific or general aspects, is an Orientalist, and what he or she does is orientalism.”[22] Within this discipline, Said produced a new distinction between ‘latent orientalism’ versus ‘manifest orientalism’. Latent orientalism was described as the predisposed ideas of the Orient which the West has regurgitated to such a grave extent that they are now heavily engrained to be the norms of the East.[23] Descriptions of primitiveness, irrationality and eccentricity are therefore covered by this area. There is an ‘unconscious positivity’ and subsequent permanence of his Oriental knowledge [24] Hence, even if our attitudes towards it change overtime, it will continue to live on as the general notions of orientalism.[25] In contrast, manifest Orientalism refers to different understandings of the Orient.[26] It covers any varying views, changes or criticisms in knowledge that may arise as a result of time period or the nation at hand. Manifest orientalism breaks away from the fixed ideas to capture diverse understandings of the Orient. It is approaches like these that paint clearer pictures of who the orient was. Said’s broad definition facilitates such ideas. Occident versus Orient The most common understanding of orientalism is the concept of self versus other. Said defines this as “an ontological and epistemological distinction made between orient and occident”.[27] This is done through the process of othering, where the Orient is pinned against the narrow scope of Western standards so as to deem them lesser than. It labels the Occident as familiar or normal and the Orient as strange.[28] Said points out that the West sees this process of othering as their duty to represent the East. This is evidenced in the following two quotes “They cannot represent themselves; they must be represented” (Karl Marx) and “the East is a career” (Benjamin Disraeli) that Said uses to open his book.[29] Hence, a universal understanding of the Orient was developed whereby its inhabitants were labelled as gullible, dangerous and in need of being tamed. This created what Said refers to as a “binary opposition” between the Orient and Occident where the respective inferiority and superiority of these groups was seen as natural. Said notes that this distinction is reinforced by what he calls “imaginative geography” where the Occident places a geographical boundary between the West and East and treats it as though it were real.[30] Said also considers the textual attitudes towards these representations and highlights how Orientalist writers readily accepted and replicated this binary opposition without question. Thus, he is critical of the ‘literature of the empire’ and its role in bringing legitimacy to these fallacies. A key idea introduced by Said was an analysis of the literature of the empire which he called a “worldly criticism”[31]. Here Said broke away from the acceptance of unilateral approaches and instead looked at the wider context within which the work was published. Hence, in a similar way to that of Foucault, we began to see discourse being questioned and history being deconstructed. It can therefore be said that Orientalism involved a necessary abandonment of this universal “other” that Western literature had solidified. Said produced a new definition of orientalism as “a manner of regularized writing, vision and study dominated by imperatives, perspectives and ideological biases ostensibly suited to the Orient.”[32] This maintained that representations of the Orient should instead be made by the orients themselves and then transferred into Western literature, rather than the other way round. Said, Foucault & Power Lastly, Said defined orientalism as a system of Western Domination. This idea is arguably where Orientalism had its greatest impact because it built on Foucault’s idea that knowledge of a particular object produces a right to domination power.[33] Said notes that orientalism became so authoritative over the Eastern constructions, that one could not produce literature without taking into consideration the limitations in thought it demanded.[34] Said believed that the West did not formulate discourse revolving around the Orient with the genuine intention of trying to understand who they are, but rather to increase control over the East. Orientalism and its literature comprised a tool that served to legitimise colonialism. This ties with Antonio Gramsci’s use of “hegemony”, discussed by Said, where the coloniser saw colonialism as a way of improving Eastern societies and believed that the Orient would recognise its benefits.[35] Foucault also noted that while discourse can work to produce power, it can also have the effect of undermining it.[36] Within Said’s work there is the idea that a reinvention of representations of the East by the East would lead to the erosion of Western domination. Said’s Influence on Postcolonialism Said’s work can be said to have inaugurated a new study as it led to the development of the field of Postcolonialism. This is evident when one considers that this field only became prominent in the 1980s, shortly after Said’s book was published. Additionally, the influence of Orientalism is clear when we look at the parallels between its core ideas and the filed of Postcolonialism. As highlighted by Edmund Burke and David Prochasaka, Said understood the history of the West and East to be co-dependent and thus not to be theorised from a unilateral perspective[37]. The multilateralism Said called for is now embraced in postcolonial studies which examine literature from Africa, the Caribbean and others.[38] Furthermore, as S.R. Moosavinia et al rightfully point out, Said looked at how the Orient-Occident relationship judged the East by European ideals to turn them into the ‘other, and a more “worldly critique” of literature is a key theme of postcolonial work. Such strides can be seen in the work of by theorists such as Dipesh Chakrabarty and his idea of “provincializing Europe”, where history is rewritten to include the “politics of despair” acknowledging the tragedies and contradiction that have arisen through Western civilisation. [39] Moreover, Said’s Orientalism can be said to have inaugurated a new kind of study because it saw the emergence of travel writing as a means of understanding colonialism.[40] Travel writing can be defined as “any account of a journey or description of a place that is based on first-hand experience.”[41] Prior to Said, there was a negative connotation attached to it because was generally understood to be a tool that fuelled and gave justifications for the expansion of colonialism. For example, Lord Cromer’s writings about his travels in Egypt, which portrayed the Orient as an irrational being in need of civilisation.[42] On the other hand, Justin Edwards discusses how Said saw the potential in travel writing as a tool that presents the multidimensional nature of the people and places visited.[43] And indeed, this idea has been adopted by subsequent theorists such as Inderpal Grewal who employed it in challenging assumptions about ‘unitary identities of nation, class, sexuality or gender’[44]. Similarly, Avtah Brah uses travel writing to explore transnational movements, diaspora and migration.[45] We thus see an expansion of Said’s ideas to touch on other key topics within postcolonialism. The influence of Orientalism is also evident when we examine the course structures of current Postcolonial Studies courses. The University of London’s School of Oriental and African Studies, one of the leading institutions in Europe in Asian, African and Middle Eastern studies, offers a Postcolonial Studies Masters Course which notes orientalism as a key area that needs to be understood.[46] Thus, highlights its foundational nature to the field. ARGUMENTS AGAINST SAID’S ORIENTALISM INAUGURATING A NEW STUDY While Orientalism presents highly thought-provoking points, the question on whether these ideas are actually “ground-breaking” enough to be deemed the start of a new study is often debated. There are will consider three main arguments against Orientalism inaugurating a new study and compare them to the definition of “inaugurate”. The main argument against Said’s work inaugurating this new study is the fact that he was not the first to criticize Western orientalism nor to attempt to reinvent our ideas of the East. Such discussions have taken place in Eastern academia since the early 1700s. A prime example is the literature of the 18th century writer Abd al-Rahman al-Jabarti who is often recognised as one of the greatest Eastern historians due to his work in depicting the realities of French Occupation and Ottoman Egypt.[47] Said’s work called for a retelling of history from the Eastern perspective, and also dealt with French and British understandings especially in regard to Egypt. Hence, it would have been useful for Said to draw upon Eastern historians such as al-Jabarti. Similarly, Abdul Latif Tibawi, an Eastern academic, published a book before Said which critiqued orientalism and aimed to “take of a few of the fads in the works of Orientalists which fall short of scientific historical standards.”[48] Said’s seeming lack of consideration for the work of Eastern writers raises questions about how genuine his aims were in ensuring that accurate representations of the East were presented. Moreover, not only did Said’s work fail to interact with Eastern Orientalists, it also failed to acknowledge previous criticisms of orientalism presented in Europe. The roots of these criticisms can be found in the post-World War II movements for anti-imperialism, nationalism and decolonization with the prominence of such stemming from the French Speaking world and their moves to decolonise history.[49] This work is epitomised Frantz Fanon, whose work was heavily focused on the idea of Self versus Other and “othering” as a binary opposition of the West and the rest,[50] and there is a clear replication of the same idea in Said’s work. Additionally, whilst Said’s work focused on French works, he missed the opportunity to bring a chronological development of the strides made against Western understandings that would have made for a more cohesive work. This supports Burke and Prachaska’s point that “Orientalism… failed to consider the political contexts in which they arose.”[51] While these are valid criticisms of Said’s work, we also need to look at the definition of ‘inaugurate’ itself. The Cambridge Dictionary definition of ‘inaugurate’ is something which ‘mark[s] the beginning of a new period, style or activity’.[52] So despite the fact that some key ideas did not originate in his work, Said’s Orientalism can still be seen to have marked the beginning of a new period of postcolonial study, since it gained significant impetus after his work. It is also important to note that in subsequent work Said himself stressed that he was not the first to discuss these ideas.[53] But, it can also be said that it the first time these ideas were widely recognised by the West. Peter Lang outlines that Orientalism’s ascendance arises “not only because of Said’s location as an eminent Professor… situated between the two worlds or East and West, but also because of his…stunning erudition.”[54] Said’s work provided a happy medium between the aforementioned ideas as it was still technically an eastern perspective of orientalism without the geographical constraints often felt by Eastern writers within that time period. Malise Ruthen further notes that “Orientalism appeared at an opportune time, enabling... academics from non-western countries to take advantage of the mood of political correctness it helped to engender.”[55] His work paved the way for other Eastern academics to produce literature and gain recognition within the field, as evidenced by the works of Middle Eastern writers such as Aijaz Ahmad, who explored the literature revolving around the so-called ‘Third World’.[56] Thus, Said’s goal of ensuring accurate representations of the East is reaffirmed as his publication led to more diverse works being recognised within the field. Another argument which undermines Orientalism’s being deemed inaugurate a new field of study is that it can be seen as essentially a repetition of Foucault’s theory. The basis of Said’s work mirrors Foucault’s critical understandings of discourse[57] and adopts the idea of strategy of discontinuity introduced in “The Archaeology of Knowledge” where Foucault eschews traditional understandings and rather looks at the “breaks and ruptures” which fail to conform.[58] This strategy also fuelled Said’s pointing out differences in representations and history. With this in mind, it could be said that Said’s work did not create anything new, but is simply an application of Foucault’s theory to a specific area, the East. Moreover, the fact that Said chose to rely on this Eurocentric theorist as the basis for his arguments against Eurocentric literature presents an interesting juxtaposition, as do his references to Gramsci, yet another Eurocentric writer. However, whereas some see this as an issue, Patrick Williams and Laura Chrisman believe that merging the distinct works of Foucault and Gramsci is one reason why Said’s work has been so successful.[59] It can also be said that Said’s work considered key concepts that Foucault failed to consider. Said himself noted that “unlike… Foucault…I do believe in the determining imprint of individual writers upon the otherwise anonymous collective of body of texts constituting a discursive formation like Orientalism”[60], thus highlighting a difference between in the two. Ferial Ghazhoul supports this view, stating that in comparison to Foucault, Said’s “conceptual framework…. is much richer, bringing in some insights from an enlightened… sociology of knowledge, a discipline mistrusted by Foucault.”[61] Hence, Said can be seen as bringing a clarity to Foucault’s work and restructuring it in a manner that would be useful to the postcolonial field. The Cambridge dictionary also defines “inaugurate” to mean ‘to put something into use or action officially’[62]. Bearing the aforementioned points in mind, it can be said that Said did inaugurate a new study as his work officially put Foucault’s theory to use in Oriental studies and the wider field of postcolonialism. This point is also supported by Ghazhoul who described Foucault’s work as “most operative” in Orientalism.[63] Another key criticism of Said’s Orientalism is that it fails to recognize gender. As alluded to by Valerie Kennedy, this omission contradicts much of what Said’s work stood for, as he has apparently sought to voice the opinions and grievances of underrepresented minority groups.[64] This observation is amplified by the fact that the West’s portrayals of an oversexualised Orient who were often linked to being very “feminine, erotic and exotic.”[65] Kennedy also notes the irony of Said’s omission by highlighting the parallels between feminism and orientalism” as they both strive to work towards dismantling the idea of women and the Orients respectively as the “other”.[66] Thus, the contradiction within Said’s theory, paired with the consequential neglect of women, evidences a lack of well-rounded, coherent conceptualisation. However, while this omission is a grave loophole in Said’s work, it does not negate the idea that Said’s work created a new area of study. SAID’S INFLUENCE ON OTHER POSTCOLONIAL THEORISTS The inaugural nature of Said’s Orientalism is also confirmed by the fact that its successors have acknowledged it as doing such. Williams and Chrisman literally state “Edward Said’s Orientalism… single-handedly inaugurates a new area of academic inquiry: colonial discourse”.[67] As alluded to throughout this essay, this idea is reinforced by the fact that it has been interacted with and expanded by other theorists. Two key examples are evidenced by the literature of Homi Bhabha and Gayatri Chakravorty Spivak. Indeed, Said, Bhabha and Gayatri have been recognised as the “holy trinity” of postcolonial theory.[68] Homi Bhabha Bhabha was extremely vocal about his belief in Said as inaugurating a new study and its provision of a base for his writing.[69] Bhabha’s work is often credited with addressing the limitations of and building on underdeveloped points in Said’s work. For example, Antony Easthope notes that Bhabha questioned the fixity of power and discourse within Said’s theory as something that is only possessed by the West.[70] He believed Said may have oversimplified the binary opposition between Orient and Occident. Hence while Bhabha follows in Said’s footsteps in considering representations and authority, he derogates from Said’s opposition and focuses more on similarities between the West and East. Correspondingly, his key contribution to postcolonialism stems from his approach to the heterogeneity of colonial and postcolonial experience.[71] He used concepts of hybridity and mimicry to acknowledge the merging of cultures and identities that arise as a result of imperial interactions. Hence, while being critical of Said, he also worked towards Said’s goal of multilateralism by producing a different outlook to the Orient-Occident relationship. Gayatri Spivak Gayatri Spivak has also credited Orientalism as being “the source book in our discipline”.[72] Though he is not explicitly mentioned throughout, an analysis of Gayatri Spivak’s work demonstrates Said’s influence through her focus on the epistemic violence against the colonised that arises as a result of othering and altering the representations of the subaltern in history.[73] Furthermore, Spivak filled the aforementioned gap within gender and orientalism by applying a feminist perspective noting that “if… the subaltern has no history and cannot speak, the subaltern as a female is even more deeply in shadow”.[74] Her built on Said’s work by broadening the scope of Eastern representation through her ‘female subaltern consciousness.[75] Japan Many Japanese theorists believe that Said’s theory “enabled non-Western countries… to participate in the ongoing discussions of literary theory.”[76] An analysis of Japan’s relationship with Said’s Orientalism provides a unique outlook. This is due to the fact that while its geographic location categorises it as the Orient, its history of colonialism also classifies it as the Occident.[77] Thus in an attempt to fit with Said’s understanding, Japanese Orientalists developed the idea of “changeability between the subject and object” that allows Japan and other countries in similar situations to alternate being the coloniser and colonised when applying the principles of Said’s Orientalism.[78] This development thus reaffirms the importance of Orientalism as Japanese scholars felt inadvertently obligated to establish a new approach to ensure that Said’s ideals could be applied. The reasoning behind outlining these theories is to showcase how Said’s work became the starting point for discussions of orientalism. So, regardless of whether theorists agree with his work, the key themes he introduced have become so heavily entrenched within colonial discourse that one cannot discuss orientalism without at least alluding to his ideas. CONCLUSION Edward Said’s Orientalism transformed the understandings of the Orient. His theories regarding the depictions of the East in literature and the subsequent authoritative measures it produced have worked to challenge previous approaches and attitudes to colonial discourse. While we cannot deny flaws in Said’s book, especially as it relates to the lack of engagement with gender, what is undeniable is the influence Orientalism had in moulding what we now know today as postcolonial studies. This influence is reflected not only in the key aims of postcolonialism, but also in the interactions of subsequent theorists with his work. Thus, it is clear that Edward Said’s Orientalism inaugurated a new kind of study of colonialism. [1] Borocz, Jozsef & Sarkar, Mahua “Colonialism” in the Encyclopedia of Global Studies (Jan 2012) pg. 229 <https://www.researchgate.net/publication/288839786_Colonialism> (accessed 26/04/2021) [2] Oxford Bibliographies’ “Postcolonial Theory” (15/01/2019) <DOI: 10.1093/OBO/9780190221911-0069> (accessed 26/04/2021) [3] Sawant, Datta “Perspectives on Postcolonial Theory: Said, Spivak and Bhabha” (October,2011) <https://www.researchgate.net/publication/271633479_Perspectives_on_Post-colonial_Theory_Said_Spivak_and_Bhabha> (accessed 26/04/2021) [4] Al Jazeera English’s “Edward Said: ’Out of Place’ (21/11/2018) <https://www.youtube.com/watch?v=CoeymZ6-LnY> (accessed 24/04/2021) [5] Mahboob, Thaha “’Orientalism’: Paving the Way for Post-colonial Studies (16/09/2018) <https://thecompanion.in/orientalism-paving-the-way-for-post-colonial-studies/> (accessed 26/04/2021) [6] Said, Edward “Orientalism” (London: Penguin, 2003) [7] Rudyard Kipling’s “The White Man’s Burden” (Feb 1899) <http://www.kiplingsociety.co.uk/poems_burden.htm> (accessed 27/04/2021) [8] Hernandez, Bonar “The Las Casas-Sepulveda Controversy: 1550-1551” (2000) pg.95 <https://history.sfsu.edu/sites/default/files/images/2001_Bonar%20Ludwig%20Hernandez.pdf> (accessed 26/04/2021) [9]Ibid. pg.99 [10] Benattar, Ilan. “Diderot’s Supplement au Voyage de Bougainville: A Study in Historical Precociousness” (20/06/2018) pg.3 <https://www.binghamton.edu/history/docs/bing-journal-history-vol13.pdf> (accessed 27/04/2021) [11] The Conversation’s “Explainer: The myth of the Noble Savage”(25/02/2016) <https://theconversation.com/explainer-the-myth-of-the-noble-savage-55316> (accessed 01/05/2021) [12] Roddan, Hector. “‘Orientalism is a Partisan Book’: Applying Edward Said's Insights to Early Modern Travel Writing” (13/04/2016)<https://doi.org/10.1111/hic3.12307> (accessed 27/04/2021) [13] n(6)Pg.40 [14] n(6)pg.33 [15] n(6)pg.32 [16] n(6) pg.36 [17] n(6)38-40 [18] N(6) pg.1 [19] Adams, Rachel “Michel Foucault: Discourse” (17/11/2017) <https://criticallegalthinking.com/2017/11/17/michel-foucault-discourse/> (accessed 01/05/2021) [20] Foucault, Michel “The Order of Things” (1966, Editions Gallimand) pg.51-84 [21] Al Mtairi, Naifa “Edward Said:Post-colonial Discourse and Its Impact on Literature” (29/01/2019) English and Linguistics Research Vol. 5 No.1 pg.3 <https://www.researchgate.net/publication/330711707_Edward_Said_Post-colonial_Discourse_and_Its_Impact_on_Literature> (accessed 01/05/2021) [22] n(6)pg.2 [23] n(6)Pg.205 [24] n(6) pg.23 [25] n(22) [26] n(23) [27] n(22) [28] n(6) pg.43 [29] n(6) [30] n(6) Chapter 1 Part II [31] Burke, Edmund & Prochaska, David “Geneaologies of Orientalism: History, Theory, Politics”(University of Nebraska Press,2008) pg 7 [32] n(6) pg.202 [33] n(19) [34] n(6) pg.3 [35] n(21) pg. 4 [36] n(22) [37] n(31) pg.32 [38] The University of Kent’s “Postcolonial Studies- PHA, MA” <https://www.kent.ac.uk/courses/postgraduate/236/postcolonial-studies> (accessed 02/05/2021) [39] Chakbraty, Dipesh “Provincializing Europe” (Princeton University Press, 2000) [40] Aune, M. G. “Early Modern European Travel Writing after Orientalism.” Journal for Early Modern Cultural Studies, vol. 5, no. 2, 2005, p.121 <www.jstor.org/stable/40339554> (accessed 02/05/2021) [41] Pettinger, Alasdair “Travel Writing” (31/07/2019) <https://www.oxfordbibliographies.com/view/document/obo-9780199846719/obo-9780199846719-0119.xml> (accessed 02/05/2021) [42] n(17) [43] Edward, Justin “Postcolonial Travel Writing and Postcolonial Theory” in Clarke, Robert “Cambridge Companion to Postcolonial Travel Writing (Cambridge University Press,2018) pg.4 <https://core.ac.uk/download/pdf/96774764.pdf > (accessed 01/05/2021) [44]Grewal, Inderpal “Home and Harem: Nation, Gender, Empire and the Cultures of Travel (Duke University Press, 1996) [45] Brah, Avtah “Cartographies of Diaspora: Contesting Identities” (Routledge 1996) [46] University of London’s School of Oriental and African Studies’ “MA Postcolonial Studies” (2021) <https://www.soas.ac.uk/languages-cultures-linguistics/programmes/mapostcolstud/> (accessed 28/04/2021) [47] Ruiz, Mario “Orientalist and Revisionist Histories of ‘Abd al-Rahman al-Jabarti”, Middle East Critique Vol 18. No.3 Autumn, 2009 pg. 261 <https://doi.org/10.1080/19436140903237061> (accessed 02/05/2021) [48] Tibawi, Abdul “English Speaking Orientalists: A critique of their approach to Islam and Arab Nationalism (Islamic Centre, 1965) p. 15 [49] n(31) p.14-15 [50]Al Saidi, Afaf “Post-colonialism Literature the Concept of Self and the other in Coetzee’s Waiting for the Barbarians: An Analytical Approach” Journal of Language Teaching and Research Vol.5 No.1, Jan 2014 pg. 95 <https://www.academypublication.com/issues/past/jltr/vol05/01/12.pdf> (accessed 03/05/2021) [51] n(50) [52] The Cambridge Dictionary’s ‘inaugurate’ <https://dictionary.cambridge.org/dictionary/english/inaugurate> (accessed 01/05/2021) [53] Said, Edward “Orientalism Reconsidered “ Cultural Critique no.1 (1985) <www.jstor.org/stable/1354282.> (accessed 04/05/2021) [54] Burney, Shehla. “Chapter One: Orientalism: The Making of the Other.” Counterpoints, vol. 417, 2012, pg 32-33<www.jstor.org/stable/42981698>. (accessed 01/05/2021) [55] The Guardian’s ”Edward Said: Controversial literary critic and bold advocate of the Palestinian cause in America” (26/09/2003) <https://www.theguardian.com/news/2003/sep/26/guardianobituaries.highereducation> (accessed 01/05/2021) [56] Aijaz, Ahmad. In Theory: Classes, Nations, Literatures. (London: Verso, 1994) [57] n(20) [58] Foucault. Michel “The Archaeology of Knowledge”(Editions Gallimard, 1969) pg.9 [59] Williams, Patrick & Chrisman, Laura “Colonial Discourse and Post-colonial Theory” (1994, Routledge) pg. 6 [60] n(6)pg.23 [61] Ghazoul, Ferial “Edward Said and Critical Decolonization” (The American University in Cairo Press, 2007) pg.100 [62] n(53) [63] n(62)pg.98 [64] Kennedy, Valerie “Edward Said: A Critical Introduction” (2000, Polity Press) pg.6 [65] Herath, Thisaranie “Women and Orientalism: 19th Century Representations by European Female Travellers and Ottoman women” (10/01/2016) p.32 <https://doi.org/10.29173/cons27054> (accessed 27/04/2021) [66] n(65) pg. 7 [67] N(60)p.5 [68] Moore-Gilbert, Bart “Postcolonial Theory” (1st Edn, Verso, 1997) pg.1 [69] Ibid p.34 [70] Easthope, Anthony “Bhabha, hybridity and identity” in Textual Practice Vol 12 No 2 (1998) pg.341 <https://doi.org/10.1080/09502369808582312> (accessed 01/05/2021) [71] n(65)pg.118-123 [72] n(72 [73] Spivak, Gayatri “Can the Subaltern Speak?” (1988) pg 24-25 <https://jan.ucc.nau.edu/~sj6/Spivak%20CanTheSubalternSpeak.pdf> (accessed 01/05/2021) [74] Ibid pg.28 [75] N(65) pg. 125 [76] Nishihara, Daisuke, and ﻧﻴﺸﻴﻬﺎﺭﺍ ﺩﺍﻳﺴﻮﻛﻲ. “Said, Orientalism, and Japan / ﺳﻌﻴﺪ ﻭﺍﻻﺳﺘﺸﺮﺍﻕ ﻭﺍﻟﻴﺎﺑﺎﻥ.” Alif: Journal of Comparative Poetics, no. 25, 2005, pg. 244 <www.jstor.org/stable/4047459> (accessed 01/05/2021) [77]Ibid [78] Ibid. pg. 249